Reciprocity in labor market relationships: Evidence from an experiment across high-income OECD countries - Israel Waichman; Ch'ng Kean Siang; Till Requate; Aric P. Shafran; Eva Camacho-Cuena; Yoshio Iida; Shosh Shahrabani (Games, 2015)
We study differences in behavior across countries in a labor market context. To this end, we conducted a bilateral gift-exchange experiment comparing the behavior of subjects from five high-income OECD countries: Germany, Spain, Israel, Japan and the USA. We observe that in all countries, effort levels are increasing while rejection rates are decreasing in wage offers. However, we also find considerable differences in behavior across countries in both one-shot and repeated relationships, the most striking between Germany and Spain. We also discuss the influence of socio-economic indicators and the implications of our findings.
Keywords: D03; C91; D81; 330; gift exchange; reciprocity; cross-country; economic experiment; labor market